Assessment of the health needs of Syrian refugees in Lebanon and Syria’s neighboring countries - Nour El Arnaout; Spencer Rutherford; Thurayya Zreik; Dana Nabulsi; Nasser Yassin; Shadi Saleh (Conflict and Health, 2019)
Abstract Background Health needs of displaced Syrians in refugee hosting countries have become increasingly complex in light of the protracted Syrian conflict. The primary aim of this study was to identify the primary health needs of displaced Syrians in Iraq, Jordan, Lebanon, Turkey, and Syria. Methods A systematic review was performed using 6 electronic databases, and multiple grey literature sources. Title, abstract, and full text screening were conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The target population was Syrian individuals displaced due to conflict in Syria and its neighboring countries. The outcomes of interest were health needs (i.e. health problems that can be addressed by health services), gaps in health services, training, and workforce. Studies on mixed refugee populations and Syrians displaced prior to the conflict were excluded. Results The Lebanon-specific results of the review were validated through two stakeholder roundtable discussions conducted with representatives from primary healthcare centers, non-governmental organizations and humanitarian aid agencies. A total of 63 articles were included in the analysis. Mental health and women’s health were identified as the greatest health needs in the region. The most common health problems were Non-communicable diseases in Jordan, women’s health in Lebanon and mental health in Turkey. Studies addressing gaps in services found the highest gap in general healthcare services, followed by women’s health, mental health, and vaccinations. Sub-optimal training and availability of health workers was also noted particularly in Syria. Results from the stakeholders’ discussions in Lebanon showed communicable diseases, women’s health and mental health as the main health needs of Syrian refugees in Lebanon. Reported barriers to accessing health services included geographical barriers and lack of necessary awareness and education. Conclusion There is a need for an enhanced synchronized approach in Syria’s refugee hosting neighboring countries to reduce the existing gaps in responding to the needs of Syrian refugees, especially in regards to women’s health, mental health, and communicable diseases. This mainly includes training of healthcare workers to ensure a skilled workforce and community-based efforts to overcome barriers to access, including lack of knowledge and awareness about highly prevalent health conditions.